Aortic dissection in the ED: a medico-legal perspective on diagnostic delays and failures - Fortier, Jacqueline H.; Mostafapour, Mehrnaz; Ohle, Robert; Barbosa, Kate; Liu, Richard; Guo, Ming; Garber, Gary E.; Murray, Heather E. (Canadian journal of emergency medicine, 2025)
Aortic dissection is a life-threatening emergency and delayed or missed diagnoses can result in significant morbidity and mortality for patients. We conducted a quantitative and qualitative analysis of medico-legal cases from a national repository involving thoracic aortic dissection seen in the emergency department during a 10-year period. We thematically analyzed peer expert criticism of the care in these cases, including provider, team, and systems factors related to diagnostic issues. We also applied two clinical decision tools to explore whether use of these tools could have affected the diagnostic process. Of 3,531 medico-legal cases in the emergency department during our study period, just 43 were related to aortic dissection. Patients were primarily male (68.2%), presented for care at large urban centers (65.1%), and were triaged as urgent or emergent (72.1%). Thirty-six patients died of their aortic dissection. A thematic analysis identified atypical presentations, diagnostic anchoring, misinterpretation or misuse of tests, communication breakdowns, and resource limitations as common in these cases. Missed diagnoses of aortic dissection in the ED often result from a combination of cognitive, communication, and system-level factors. Understanding these contributors can inform evidence-based, systems-level supports and strategies to enhance diagnostic accuracy and reduce patient harm.